BURDEN AND DETERMINANT FACTORS OF ANEMIA AMONG ELEMENTARY SCHOOL CHILDREN IN NORTHWEST ETHIOPIA: A COMPARATIVE CROSS SECTIONAL STUDY - Feleke, Berhanu Elfu; Derbie, Awoke; Zenebe, Yohannes; Mekonnen, Daniel; Hailu, Tadesse; Tulu, Begna; Adem, Yesuf; Bereded, Fetlework; Biadglegne, Fantahun (African Journal of Infectious Diseases (AJID), 2017)
Background: Anemia is an indicator of both poor nutrition and health. In low-income countries like Ethiopia, the prevalence of anemia remains high due to several determinant factors. There is a lack of regular surveillance system to determine the magnitude of anemia among school age children. The aim of this study was to determine the burden and determinant factors of anemia among school children. Materials and Methods: A comparative cross-sectional study was conducted from March 2014 to May 2014 among elementary school children in Northwest Ethiopia. Multi stage and simple random sampling techniques were used to select the schools and the study subjects. Standard questionnaire was employed to assess the socioeconomic status of study participants. Intestinal parasitosis infections and hemoglobin level were determined by formula ether concentration technique and automated hematology analyzer, respectively. Descriptive statistics were used to determine the burden of anemia. Stepwise logistic regression was used to identify the determinants of anemia. Results: Among 2,372 elementary school children, the prevalence of anemia was 7.6% (95 % CI: 7% - 9%). The mean hemoglobin level was 11.6 g/dl ranging from 10 g/dl to 13g/dl. The magnitude of hookworm infection was 530 (22.3%). In multivariate analysis anemia was found associated with residence, source of water, availability of latrine, maternal education, family size and hookworm infection. Conclusion: Anemia still remains as a major public health problem among the school children in the study area. Residence, source of water, availability of latrine, maternal education, family size and hookworm infection are also the major determinant factors for the high prevalence of anemia. Therefore, health education, iron supplement and deworming should be given to school age children.